Analysis and Design of Asset and Non-Asset Lending Information Systems in the Informatics Engineering Service Unit at Astra Polytechnic - Haikal Andrean; Indah Cyithia Devi; Fadhilah Nur’aini; Michael Edigia Wizard (Engineering, MAthematics and Computer Science Journal (EMACS), 2023)
The development of information technology is developing rapidly and has a positive impact on organizational, one of which is Astra Polytechnic, especially at UPT Informatics, which supports the operational activities of inventory lending in the form of assets and non-assets which are considered inefficient. The process of recording, submitting, and approving inventory loans is still done manually, so it takes a lot of time and is prone to errors. The process of recording inventory data is still using excel, loan applications are still made using hardcopy forms and there are no asset and non-asset reports. The aim of research is to analyze needs and design of a system for lending assets and non-assets at UPT Informatics based on Web Applications in order to overcome these problems. The design uses System Development Life Cycle (SDLC) based on Prototyping methodology until design stage. The process of analysis and design is explained using Unified Modeling Language (UML) approach. Analysis of system requirements is carried out on ongoing business processes, which are then outlined in design of asset and non-asset lending information systems, especially in documentation process to produce reports according to company needs.